Verification of dyspnea according to external respiratory function in patients with bronchial asthma - Ruziyeva A.A; Ishankulova D.K.; Nizomov B.U (Research Parks Publishing LLC, 2021)
Due to the widespread and rapid rate of damage to the bronchopulmonary system, bronchial asthma (BA) will always remain the most urgent task of medicine. This study was conducted to determine the type of dyspnea, for verification of which the method of assessing the functional state of external respiration-Spirography-was used. A survey of 93 patients with AD, whose age ranged from 31 to 63 years, was conducted. In 71 (76.3%) patients with severe BA, and in 15 (16.1%) and 7 (7.6%) patients with moderate and mild BA, respectively. The basis for determining the violation of the ventilation function of the lungs for obstructive BA with a mild and moderate course, as well as a mixed type in severe BA, was the data of indicators of the external respiratory function (FVD).